PELATIHAN PEMBUATAN SABUN CAIR DAN SABUN TRANSPARAN DI KENAGARIAN PASIE LAWEH - Demi Ramadian; Hartami Dewi; Zulhamidi; Rizki Alfi; Amris (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Community service has been carried out in Jorong Babussalam, Kenagarian Pasie Laweh, Sungai Tarab District, Tanah Datar District. This activity is intended for housewives and teenagers, amounting to 20 people. The public was given knowledge and training to make liquid soap and transparent soap. This activity is expected to increase the knowledge and skills of the community to make transparent soap and make business opportunities that might be done by the community so as to improve the family economy. This activity is carried out in the form of workshops with lectures and practices.